ANALISIS PROSEDUR PELELANGAN TERHADAP BARANG JAMINAN PADA KANTOR PT. PEGADAIAN CABANG SUNGGUMINASA KABUPATEN GOWA - Bunyamin Bunyamin (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aims to determine the auction procedure against collateral and guarantees the effectiveness of the auction items at PT. Pegadaian Branch Sungguminasa in Gowa. the method used is descriptive analysis method that depict or describe systematically, factual and accurate information on the facts in the practice of auctions conducted by PT. Sungguminasa pawnshop branches in Gowa. Discussion The results of the analysis on the auction procedure to the collateral that has been done by PT. Pegadaian Branch Sungguminasa in Gowa was in accordance with the procedures of the company. collateral in the tender process in PT. Branch Office Sungguminasa auction in Gowa was appropriate standard auction procedures this can be seen from a guidebook or guidelines that exist in the company.